(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article presents the results of questionnaires to determine the professional interest of secondary school students in the field of physical culture and sports, the results of research on the methodology developed to prepare them for higher education in this field and the effectiveness of their implementation.